ChemInform Abstract: Copper‐Catalyzed Direct N‐Arylation of N‐Arylsulfonamides Using Diaryliodonium Salts in Water. Issue 51 (23rd December 2014) - Geng, Xu; Mao, Song; Chen, Liangshun; Yu, Jianjun; Han, Jianwei; Hua, Jianli; Wang, Limin
Abstract In some cases, better yields are obtained in dichloromethane as solvent.